The Techniques of Teaching Speaking to the 8th Grade Students of SMP IT Asy Syadzili Pakis Malang - Muhammad Yasminto; M. Agus Susanto (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2022)
Technique of teaching is one of the important parts of learning English speaking. Therefore, it is expected that a professional teacher have a great knowledge of the effective techniques of teaching. In this study, the researchers discuss the techniques of teaching speaking to the 8th grade students of SMP IT Asy Syadzili Pakis Malang. One of the researchers is an English teacher and as an interviewee. One researcher investigated the teaching-learning process in English speaking because he wanted to find out and describe the techniques used by the English teacher of the 8th grade in teaching speaking in which the English teacher is the second researcher as a form of research collaboration. The data of this study were collected by using (1) observation check-list; (2) a set of questionnaire sheet; and (3) interview guide. A set of questionnaire sheet was written in English, and then it was given to the English teacher. The data source was only an eighth grade English teacher who could give the required information to answer the research problems. The results showed the teacher developed the syllabus based on the curriculum, and the syllabus supported the teaching learning process and ran successfully. Having conducted the interview to the teacher concerning with the techniques of teaching speaking, showed that the result of interview from the teacher can bee seen from the questionnaire check-list involving all the techniques used by the English teacher to teach speaking. One of techniques that the teacher used was asking question by using English. It means that he always gives the motivation to speak English bravely. Dialogue with update topic, using visual aid, and English discussion are the techniques, which are often conducted by the teacher there. Sometimes the teacher uses role-play, speech, storytelling, discovery and simulation, and asking question using Bahasa. Keywords: Technique of Teaching Speaking, English Productive Skills, Speaking Ability